HUBUNGAN BABY SPA DENGAN KUALITAS TIDUR DAN FREKUENSI SAKIT PADA BAYI DI SESHA MOM AND BABY SPA - Suci Utami (Journal of Midwifery and Health Administration Research, 2022)
Background: Healthy of infants and toddlers must be considered for physical and mental growth and development, such health is influenced by intake, nutrition and good care. Baby spa is a massage therapy followed by spa health services for babies which has benefits, one of which is increasing physical growth and mental development. Sleep in infants is evenly divided during the day and night which is an adaptation process and is gradually regulated by the maturation of nerve tissue. 22% of 8-month-old babies wake up every night and 10% wake up more than 3 times. The activities of mothers as housewives and working make mothers less able to take the time to apply the exercise Sleep quality is very influential on the well-being of a child such as health. Based on the problems raised, researchers will conduct a study on The relationship between baby spa and sleep quality and frequency of pain in infants at Sesha Mom and Baby Spa in 2021. Methods: This research is a quantitative research with a correlational approach with ex-post facto data analysis.  The study population was babies who did baby spas at Sesha mom and baby spa as many as 20 with a study sample using total sampling. Results: The results showed a correlation coefficient of massage and spa frequency with sleep quality of 0.168 (positive), meaning that if the frequency of massage and spa is high, sleep quality increases. While the value of the correlation coefficient of Spa frequency with the frequency of illness -2.75 (negative) means that if the number of baby spa frequencies is high, the frequency of illness decreases.Conclusion:  R= 0.356 where R>0.05 which means the frequency of baby spa is significantly related to the frequency of pain and sleep quality. Need to conduct counseling in the form of Health Education about the benefits of baby spa for mothers who have babies.